Association between Vitamin D Deficiency and Primary Dysmenorrhea - Nusrat Fozia Pathan, Bushra Noor Khuhro, Sadia Nasir, Fahmeed Khakwani, Saira Khurshid, Muhammad Razaq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Primary dysmenorrhea is very common in younger women and often greatly impairs normal functioning. Vitamin D may affect menstrual pains’ inflammatory and muscle activity components. In young women, understand the relationship between the vitamin D level in serum and the existence and degree of primary dysmenorrhea. Methods: This cross-sectional study was conducted at the Khyber Teaching Hospital, Peshawar, from January to December 2022. Eighty-three females aged between 18 to 25 years were enrolled for the study. Information related to menstrual history, pain intensity, lifestyle, and sun exposure was gathered through a documented interview. ‘25-hydroxyvitamin D levels’ in the serum were determined using a chemiluminescence immunoassay. A numerical rating scale evaluates pain intensity. SPSS version 25 was employed for statistical analysis, with a p-value < 0.05 taken as significant. Results: Among the participants, 73.5% reported experiencing primary dysmenorrhea. ‘A significant association was found between vitamin D deficiency and the presence of menstrual pain (p=0.001)’. Additionally, mean vitamin D levels decreased progressively with increasing severity of dysmenorrhea, showing a statistically significant difference across mild, moderate, and severe pain groups (p<0.001). Conclusion: According to the findings, primary dysmenorrhea’s occurrence and severity are significantly linked to low vitamin D levels. In young women, managing and screening for vitamin D deficiency could be an easily applicable means of effectively diminishing menstrual pain. Keywords: Primary dysmenorrhea, Vitamin D deficiency, Menstrual pain, Young women, Serum 25(OH)D, Menstrual health